Positive electrode active material, electrochemical device and electronic device
A core-shell structured cathode active material with a phosphate-based sodium salt core and conductive polymer shell, integrated with a carbon substrate, addresses conductivity and performance issues in sodium ion batteries, enhancing gram capacity and cycle life.
Patent Information
- Application Number
- JP2023525473
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-06-26
- Filing Date
- 2022-03-08
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2042-03-08
AI Technical Summary
Lithium-ion batteries face issues with high costs and resource depletion, while sodium ion batteries with pyrophosphate-based cathode materials suffer from poor conductivity, affecting their gram capacity and electrochemical performance, hindering large-scale application.
A cathode active material with a core-shell structure is developed, comprising a phosphate-based sodium salt core and a conductive polymer shell, integrated with a carbon-based conductive substrate to enhance conductivity and prevent direct contact with electrolyte, thereby improving gram capacity and cycle performance.
The core-shell structure enhances the conductivity and mechanical stability of the cathode active material, reducing side reactions and improving the cycle performance and dynamic properties of sodium ion batteries.
Smart Images

Figure 0007606604000004 
Figure 0007606604000005 
Figure 0007606604000001
Abstract
Description
CROSS-REFERENCE TO RELATED PATENT APPLICATIONS
[0001] This application claims priority to Chinese patent application No. 202110742610.9, filed on June 26, 2021, entitled "Positive Electrode Active Material, Electrochemical Apparatus and Electronic Device," which is hereby incorporated by reference in its entirety. [Technical field]
[0002] The present application relates to the field of secondary battery technology, specifically to positive electrode active materials, electrochemical devices, and electronic devices. [Background technology]
[0003] As energy and environmental problems become more evident, new energy industries have become more important. Lithium-ion batteries have been widely used as important new energy storage devices in recent years due to their characteristics such as high energy density and good cycle characteristics. However, lithium-ion batteries face severe problems such as the shortage of related active material resources, the constant high battery cost, and the depletion of related resources, so there is a need to develop another low-cost metal-ion secondary battery system.
[0004] Sodium ion batteries have become a research hotspot in recent years due to their advantages of low cost, abundant sodium metal resources, and similar manufacturing process to lithium ion batteries. In sodium ion secondary battery systems, pyrophosphate-based positive electrode materials have attracted widespread attention due to their good cycle characteristics and low cost. However, pyrophosphate-based positive electrode materials themselves have poor electrical conductivity, which affects the gram capacity of pyrophosphate-based positive electrode materials when used as is, and their electrochemical performance is poor, which significantly hinders their large-scale application. Summary of the Invention
[0005] The present application provides a positive electrode active material, an electrochemical device, and an electronic device that can effectively improve the conductivity of the positive electrode active material, improve the gram capacity and dynamic properties of the material, and reduce the occurrence of side reactions to improve the cycle performance of the positive electrode active material.
[0006] In a first aspect, the present application provides a cathode active material comprising a conductive substrate and an active material having a core-shell structure comprising a core layer material and a shell layer material distributed in the conductive substrate, wherein the core layer material comprises a phosphate-group sodium salt material, the shell layer material comprises a conductive polymer, and the conductive substrate comprises a carbon material.
[0007] In some optional embodiments, the conductive polymer comprises at least one of polyaniline, polypyrrole, polymers of 3,4-ethylenedioxythiophene monomers, and polyethylene oxide.
[0008] In some optional embodiments, the positive electrode active material has at least one of the following characteristics: (1) The chemical formula of the sodium phosphate material is Na x1 R y1 (PO4) Z1 wherein 1≦x1≦3, 1≦y1≦2, and 1≦z1≦3, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb. (2) The chemical formula of the sodium phosphate material is Na x2 R y2 (P2O7) Z2 wherein 1≦x2≦7, 1≦y2≦3, and 1≦z2≦4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb. (3) The chemical formula of the sodium phosphate material is Na x3 R y3 (PO4) Z3(P2O7) k3 wherein 1≦x3≦7, 1≦y3≦4, 1≦z3≦2, 1≦k3≦4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb. (4) The chemical formula of the sodium phosphate material is Na x4 R y4 (PO4) Z4 M l1 wherein 1≦x4≦3, 1≦y4≦2, 1≦z4≦2, and 1≦l1≦3; R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb; and M includes at least one of F, Cl, and Br.
[0009] In some optional embodiments, the sodium phosphate material includes at least one of NaFePO4, Na3V2(PO4)3, Na2FeP2O7, Na2MnP2O7, NaCoP2O7, Na7V3(P2O7)4, Na2FePO4F, Na3V2(PO4)2F3, Na4Fe3(PO4)2(P2O7), Na4Co3(PO4)2(P2O7).
[0010] In some optional embodiments, the positive electrode active material has at least one of the following characteristics: (5) The shell layer material has a thickness of 50 nm to 400 nm. (6) The mass content of the shell layer material in the positive electrode active material is 1% to 10%. (7) The mass content of the core layer material in the positive electrode active material is 90% to 99%.
[0011] In some optional embodiments, the positive electrode active material has at least one of the following characteristics: (8) The carbon material includes at least one of carbon nanotubes, graphene, carbon fibers, natural graphite, and artificial graphite. (9) The carbon material contains an oxygen-containing group, and the oxygen-containing group is at least one type selected from a carboxyl group, a hydroxyl group, and an ether group. (10) The carbon material contains an oxygen-containing group, and the mass content of oxygen atoms in the carbon material is ≧0.1%. (11) The conductive substrate is a carbon material.
[0012] In some optional embodiments, the mass content of the conductive substrate in the positive electrode active material is 1% to 10%.
[0013] In some optional embodiments, the positive electrode active material has at least one of the following characteristics: (12) The positive electrode active material has a resistivity of 0.005 Ω·cm to 100 Ω·cm at a pressure of 20 MPa. (13) The positive electrode active material has an average particle size of 5 μm to 20 μm. (14) The positive electrode active material has a gram capacity of 100 mAh / g to 180 mAh / g.
[0014] In a second aspect, the present application provides an electrochemical device comprising a positive electrode sheet comprising the above-described positive electrode active material, a negative electrode sheet, a separator, and an electrolyte.
[0015] In a third aspect, the present application provides an electronic device comprising an electrochemical device as described above.
[0016] The technical solution provided in this application has at least the following beneficial effects: The present application provides a positive electrode active material in which the surface of a phosphate-based sodium salt material is coated with a conductive polymer, the conductive polymer has a relatively high mechanical strength, and the conductive polymer structure is flexible and bendable, and has good processability, and even if the volume of the material changes due to charging and discharging, the coating layer can maintain its stability and not deform. From the above, the coating layer can improve the conductivity of the phosphate-based sodium salt material to improve its gram capacity and dynamic properties, while preventing the phosphate-based sodium salt material from directly contacting the electrolyte, reducing the occurrence of side reactions, and improving the cycle performance of the positive electrode active material. By attaching the coated active material to a conductive substrate, the conductivity of the material can be further improved by utilizing the high conductive properties of the conductive substrate, and the positive electrode active material having a conductive polymer-coated structure and a conductive substrate can exhibit higher gram capacity, better dynamic properties and cycle performance. [Brief description of the drawings]
[0017] In order to more clearly describe the technical solutions of the embodiments of the present application, the drawings used in the embodiments are briefly introduced below. It should be understood that the following drawings only illustrate some embodiments of the present application, and are not to be regarded as limiting the scope of the present application.
[0018] [Figure 1] FIG. 2 is a schematic diagram showing the configuration of one type of positive electrode active material provided in the present application. [Diagram 2] FIG. 2 is a schematic diagram showing the configuration of an active material in a positive electrode active material provided in an embodiment of the present application. [Explanation of symbols]
[0019] 1-conductive substrate, 2-active material, 21-core layer material, 22-shell layer material DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be described in more detail with reference to the drawings and examples. It should be understood that the specific embodiments described herein are only for the purpose of illustrating the present application, and are not intended to limit the present application.
[0021] In the description herein, the terms "first" and "second" are used for descriptive purposes only, unless otherwise specified and limited, and should not be understood as indicating or implying relative importance. The term "plurality" means two or more than two, unless otherwise specified and explained. The terms "connected", "fixed", etc. should be understood broadly, for example, "connected" may be a fixed connection, a removable connection, an integral connection, or an electrical connection, and may be directly connected or indirectly connected via an intermediate medium.
[0022] The specific meanings of the above terms in this application can be understood by those of skill in the art in light of particular circumstances.
[0023] In the description of this specification, directional terms such as "above" and "below" described in the embodiments of the present application are described in terms of angles shown in the drawings, and should not be understood as limiting the embodiments of the present application. In addition, when the context refers to an element being connected "above" or "below" another element, it should be understood that it can be directly connected to the "above" or "below" of another element, but also can be indirectly connected to the "above" or "below" of another element via an intermediate element.
[0024] In a first aspect, the present application provides a positive electrode active material, and FIG. 1 is a schematic diagram of a positive electrode active material provided in an embodiment of the present application. As shown in FIG. 1, the positive electrode active material includes a conductive substrate 1 and an active material 2 distributed on the conductive substrate 1. The active material 2 has a core-shell structure, and FIG. 2 is a schematic diagram of the active material in the positive electrode active material provided in the embodiment of the present application. As shown in FIG. 2, the core-shell structure includes a core layer material 21 and a shell layer material 22. Among them, the core layer material 21 includes a phosphate group sodium salt material, the shell layer material 22 includes a conductive polymer, and the conductive substrate 1 includes a carbon material.
[0025] In the present application, the conductive substrate 1 is used to construct a conductive network, and the active material 2 may be adhered to the surface of the conductive substrate 1 or may be attached to the pore structure of the conductive substrate 1, but is not limited thereto. By attaching the active material 2 to the conductive substrate 1, the conductive performance of the positive electrode active material can be improved by utilizing the high conductivity of the conductive substrate 1.
[0026] In the above-mentioned solution, the conductive substrate 1 may be a carbon material, in which the carbon material may include at least one of carbon nanotubes, graphene, carbon fiber, and natural graphite. Optionally, the carbon material includes an oxygen-containing group, and the oxygen-containing group is at least one selected from a carboxyl group, a hydroxyl group, and an ether group. The mass content of oxygen atoms in the oxygen-containing group may be ≧0.1%, and optionally, the mass content of oxygen atoms in the oxygen-containing group may be specifically 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc., and is not limited thereto. By controlling the mass content of oxygen atoms in the carbon material, the overpotential of the conductive substrate 1 can be reduced, the occurrence of poor affinity between the active material 2 and the positive electrode current collector can be improved, and the adhesive strength between the active material 2 and the positive electrode current collector can be increased.
[0027] In the actual application process, the mass content of the conductive substrate 1 in the positive electrode active material may be 1% to 10%, and optionally, the mass content of the conductive substrate 1 in the positive electrode active material may be specifically 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., and is not limited here. If the mass content of the conductive substrate 1 in the positive electrode active material is too large, the amount of carbon material with a large specific surface area, no capacity, and low compaction density becomes too large, and the battery capacity becomes small, resulting in a decrease in the energy density and cycle life of the battery. If the mass content of the conductive substrate 1 in the positive electrode active material is too low, the conductive network between the active materials 2 is difficult to effectively form, the conductive speed decreases, and the conductive performance and life of the battery are reduced. Optionally, the mass content of the conductive substrate 1 in the positive electrode active material may be 4% to 8%.
[0028] In the above-mentioned scheme, the active material 2 on the conductive substrate 1 has a core-shell structure, the core-shell structure is composed of a core layer material 21 and a shell layer material 22, the core layer material 21 is coated with the shell layer material 22, the coating structure can be full coating or half coating, the coating method can be a solid-phase coating method, a liquid-phase coating method or a gas-phase coating method, etc., the specific coating method can be selected according to need and is not limited here. Optionally, the shell layer material 22 and the core layer material 21 of the active material 2 are adsorbed by the Coulombic attraction of charges, or are adhered by a strong chemical bond between the core layer material 21 and the shell layer material 22.
[0029] Optionally, the core layer material 21 may include a sodium phosphate salt material as a component thereof, the chemical formula of which is: Na x1 R y1 (PO4) Z1 , Na x2 R y2 (P2O7) Z2 , Na x3 R y3 (PO4) Z3 (P2O7) k3 , Na x4 R y4 (PO4) Z4 M l1wherein 1≦x1≦3, 1≦y1≦2, 1≦z1≦3, 1≦x2≦7, 1≦y2≦3, 1≦z2≦4, 1≦x3≦7, 1≦y3≦4, 1≦z3≦2, 1≦k3≦4, 1≦x4≦3, 1≦y4≦2, 1≦z4≦2, 1≦l1≦3, R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb, and M includes at least one of F, Cl, and Br.
[0030] Optionally, the phosphate-based sodium salt material may be specifically NaFePO4, Na3V2(PO4)3, Na2FeP2O7, Na2MnP2O7, NaCoP2O7, Na7V3(P2O7)4, Na2FePO4F, Na3V2(PO4)2F3, Na4Fe3(PO4)2(P2O7), Na4Mn3(PO4)2(P2O7), Na4Co3(PO4)2(P2O7), Na4Ni3(PO4)2(P2O7), Na7V4(PO4)(P2O7)4, etc., but not limited thereto. Optionally, the phosphate-based sodium salt material may be Na4Fe3(PO4)2(P2O7).
[0031] The shell layer material 22 used to coat the core layer material 21 includes a conductive polymer, of which the conductive polymer includes at least one of polyaniline, polypyrrole, polymer of 3,4-ethylenedioxythiophene monomer, and polyethylene oxide. The conductive polymer-coated positive electrode active material has better reversibility during the charge and discharge process. The conductive polymer shell layer has relatively strong toughness and can be uniformly coated on the surface of the phosphate-based sodium salt material, thereby improving the mechanical strength of the positive electrode active material, and the conductive polymer has relatively strong conductivity, thereby improving the conductivity of the phosphate-based sodium salt material, thereby improving the gram capacity and dynamic properties of the positive electrode active material. Meanwhile, the conductive polymer shell layer can prevent the surface of the positive electrode active material from direct contact with the electrolyte, reduce the occurrence of side reactions, and improve the cycle performance of the positive electrode active material. In the positive electrode active material, the active material 2 is supported on the conductive substrate 1, and a large amount of isolated active material 2 can be connected by a one-dimensional or two-dimensional conductive network constructed outside, thereby further improving the conductivity. In addition, the oxygen-containing functional groups of the conductive substrate 1 are increased, and the oxygen-containing functional groups are used to form stronger hydrogen bonds with the shell layer material 22 on the surface of the active material 2, thereby improving the bonding strength between the active material 2 and the conductive substrate 1.
[0032] In the actual application process, the mass content of the core layer material 21 in the positive electrode active material may be 90% to 99%. Optionally, the mass content of the core layer material 21 in the positive electrode active material may be specifically 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, etc., and is not limited here. If the mass content of the core layer material 21 in the positive electrode active material is too high, the proportion of the conductive polymer covering the core layer material 21 is too small, the conductivity of the positive electrode active material is reduced, and the gram capacity and dynamic properties of the battery are affected. If the mass content of the core layer material 21 in the positive electrode active material is too small, the proportion of the phosphate group sodium salt material with good cycle performance is too small, and the cycle performance of the battery is reduced. Optionally, the mass content of the core layer material 21 in the positive electrode active material may be 95%.
[0033] The mass content of the shell layer material 22 in the positive electrode active material may be 1% to 10%, and optionally, the mass content of the shell layer material 22 in the positive electrode active material may be specifically 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., and the thickness of the shell layer material 22 may be 50nm to 400nm, and optionally, the thickness of the shell layer material 22 may be specifically 50nm, 100nm, 150nm, 200nm, 300nm, 350nm, 400nm, 450nm, 500nm, etc., and is not limited thereto. If the mass content and thickness of the shell layer material 22 in the positive electrode active material are too high, the shell layer will be too thick, the mass ratio of the conductive polymer will be too high, and the mass ratio of the phosphate group sodium salt material with good cycle performance in the core layer 21 will be reduced, which will ultimately affect the cycle performance of the battery. If the mass content and thickness of the shell layer material 22 in the positive electrode active material are too low, the conductive polymer coating layer coated on the core layer material 21 will be too thin, the conductivity of the positive electrode active material will decrease, and the surface of the positive electrode active material will be more likely to directly contact the electrolyte, resulting in severe side reactions. Optionally, the mass content of the shell layer material 22 in the positive electrode active material may be 4% to 8%, and the thickness of the shell layer material 22 may be 100 nm to 300 nm.
[0034] As an option of the technical solution of the present application, the average particle size of the positive electrode active material may satisfy 5 μm≦Dv50≦20 μm, and optionally, the particle size of the positive electrode active material may be specifically 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 17 μm, 19 μm, 20 μm, etc., and is not limited here. If the average particle size of the positive electrode active material is too small, the aggregation phenomenon of the positive electrode active material particles is likely to occur, and the side reaction with the electrolyte becomes intense. If the average particle size of the positive electrode active material is too large, the diffusion rate of the active ions inside the positive electrode active material decreases, the dynamic properties decrease, and the performance of the positive electrode active material gram capacity and the battery cycle performance are affected. Optionally, preferably, the particle size of the positive electrode active material satisfies 8 μm≦Dv50≦15 μm.
[0035] In a second aspect, the present application provides an electrochemical device including a positive electrode sheet including the positive electrode active material described above, a negative electrode sheet, a separator, and an electrolyte.
[0036] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material of the first embodiment.
[0037] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material.
[0038] As an option of the technical solution of the present application, the negative electrode active material may include at least one of graphite, silicon material, silicon-oxygen material, tin material, tin-oxygen material or silicon-carbon composite material.
[0039] As an option of the technical solution of the present application, the negative electrode active material layer may include an adhesive, and the adhesive may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyfluoroethylene, ethylene oxygen-containing polymer, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, poly(1,1-difluoroethylene), polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, nylon, etc., but is not limited thereto.
[0040] As an option of the technical solution of the present application, the negative electrode active material layer may further include a conductive material, which may include natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, metal powder, metal fiber, copper, nickel, aluminum, silver, or polyphenylene derivatives, etc., but is not limited thereto.
[0041] As an option of the technical solution of the present application, the negative electrode current collector may include, but is not limited to, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or conductive metal-coated composite current collector.
[0042] Since sodium ions do not form an alloy with aluminum, an aluminum-based current collector is preferably used from the viewpoint of cost reduction and weight reduction. The aluminum-based current collector may include any of aluminum foil, aluminum alloy foil, and aluminum-based composite current collector. The aluminum-based composite current collector may include a polymer base film and aluminum foil and / or aluminum alloy foil formed on both sides of the polymer base film. Optionally, the aluminum-based composite current collector has a "sandwich" structure in which a polymer base film is located in the middle and aluminum foil is provided on both sides of the polymer base film, or aluminum alloy foil is provided on both sides of the polymer base film, or aluminum foil is provided on one side of the polymer base film and aluminum alloy foil is provided on the other side. The polymer base film is any one of polyamide, polyterephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, polyparaphenylene terephthalamide, ethylene propylene rubber, polyformaldehyde, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber, and polycarbonate. Optionally, in the present application, an aluminum-based composite current collector with better ductility is selected to favor the maintenance of the electrode integrity during the sodium deposition / desorption process.
[0043] As an option of the technical solution of the present application, the separator may be various materials in the art that are applied to separators of electrochemical energy storage devices, for example, may include at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fibers, but is not limited thereto.
[0044] As an option of the technical solution of the present application, the electrochemical device may further include an electrolyte, the electrolyte including an organic solvent, a sodium salt and an additive.
[0045] The organic solvent of the electrolyte according to the present application may be any organic solvent known in the prior art to be used as a solvent for electrolytes. The electrolyte used in the electrolyte according to the present application is not limited and may be any electrolyte known in the prior art. The additive of the electrolyte according to the present application may be any additive known in the prior art to be used as an additive for electrolytes.
[0046] In a specific embodiment, the organic solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate, fluoroethylene carbonate, propylene carbonate, propyl propionate, or ethyl propionate.
[0047] In a specific embodiment, the sodium salt may include at least one of an organic sodium salt or an inorganic sodium salt.
[0048] In specific embodiments, the sodium salt may include, but is not limited to, sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium difluorophosphate (NaPO2F2), sodium bis(trifluoromethanesulfonyl)imide NaN(CF3SO2)2 (NaTFSI), sodium bis(fluorosulfonyl)imide Na(N(SO2F)2) (NaFSI), sodium bisoxalatoborate NaB(C2O4)2 (NaBOB), sodium difluorooxalatoborate NaBF2(C2O4) (NaDFOB), or sodium perchlorate.
[0049] As an option of the technical solution of the present application, the electrochemical device of the present application may include, but is not limited to, all kinds of primary batteries, secondary batteries, including at least one of soft bag, rectangular aluminum case, rectangular steel case, cylindrical aluminum case, and cylindrical steel case battery.
[0050] In a third aspect, the present application provides an electronic device comprising an electrochemical device as described above.
[0051] As an option of the technical solution of the present application, the electronic device may include, but is not limited to, a notebook computer, a pen-input personal computer, a mobile computer, an electronic book player, a mobile phone, a mobile fax machine, a mobile copy machine, a mobile printer, a headphone stereo, a video recorder, an LCD television, a handy cleaner, a portable CD, a mini disk, a transceiver, an electronic organizer, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, an automobile, a motorcycle, an electric-assisted bicycle, a bicycle, a lighting device, a toy, a game machine, a clock, an electric tool, a strobe, a camera, a large-scale household storage battery, an energy storage or a sodium ion capacitor, etc. The electrochemical device may be used to supply power to the electronic device.
[0052] As a fourth aspect, the present application further provides a method for producing a positive electrode active material, the method including the following steps S10 to S30.
[0053] S10: The carbon material is placed in a solution of concentrated sulfuric acid: concentrated nitric acid = 3:1, stirred for 4 hours, washed with deionized water, filtered, and then placed in an oven and dried at 80 ° C. Among them, the pore size of the filter sieve is selected to be 400 mesh.
[0054] S20: The carbon material after the above treatment is put into water and ultrasonically dispersed, then mixed and stirred with a stoichiometric ratio of iron nitrate and sodium dihydrogen phosphate solution to be uniform, and then spray-dried to prepare precursor powder. The carbon material after ultrasonic dispersion has an average particle size of 50nm-20μm, the inlet temperature of the spray dryer is 150℃-250℃, and the outlet temperature of the spray dryer is 80℃-150℃.
[0055] S30: The precursor powder is roasted at a high temperature of 600°C for 6 hours, then added to the conductive polymer solution and thoroughly stirred, and dried at 80°C to completely remove the solvent, and the resulting product is sieved to obtain the positive electrode active material. The stirring time is 1h to 6h, and the particle size of the positive electrode active material after sieving satisfies 8μm≦Dv50≦15μm.
[0056] The final positive electrode active material is obtained by the above-mentioned manufacturing method and by adjusting the shell layer material weight fraction, the conductive substrate weight fraction, the shell layer material type, and the positive electrode active material particle size.
[0057] In order for those skilled in the art to better understand the technical solution of the present invention, the present application is described in more detail below in light of specific embodiments.
[0058] Example 1:
[0059] (1) Manufacturing of negative electrode sheets
[0060] First, the carbon material was placed in a mixed solution of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 3:1, stirred for 4 hours, washed with deionized water, filtered, and then placed in an oven and dried at 80°C. The carbon material and the polymer conductive polymer were added to dimethylpyrrolidone and stirred to form a uniform slurry. The slurry was applied to copper foil and dried to obtain the carbon material coating to be used. Sodium metal was placed in a stainless steel crucible in an Ar gas atmosphere and heated to 200°C to completely melt it. Then, the alloy component powder was added to the liquid sodium metal, and the mixture was thoroughly stirred for 2 hours to ensure uniform mixing of the metal powder and the sodium metal liquid, and cooled to obtain a sodium metal alloy active material. The sodium metal alloy active material was compounded on the surface of the carbon material coating layer by cold pressing to obtain a sodium metal negative electrode sheet.
[0061] (2) Manufacturing of positive electrode sheets
[0062] 10wt% polyvinylidene fluoride adhesive was completely dissolved in N-methylpyrrolidone, and 10wt% carbon black conductive agent and 80wt% Na4Fe3(PO4)2(P2O7) positive electrode active material were added to create a uniformly dispersed slurry. The slurry was evenly spread on the zirconium surface and transferred to a vacuum drying oven to dry completely. The resulting sheet was roll pressed and then punched out to obtain the desired wafers.
[0063] (3) Separator manufacturing
[0064] A polypropylene polymer film was employed.
[0065] (4) Manufacturing of electrolyte
[0066] Ethylene glycol dimethyl ether (DME) was used as the organic solvent, and thoroughly dried sodium salt NaPF6 was dissolved in the mixed organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L.
[0067] (5) Manufacture of button batteries
[0068] The positive electrode sheet, separator, and negative electrode sheet were stacked in order with the separator positioned between the positive electrode sheet and the negative electrode sheet to function as an insulator, and the electrolyte was added to assemble a button battery.
[0069] Specific parameters of Examples 1 to 22 and Comparative Examples 1 to 7 produced by the above-mentioned methods are shown in Table 1. [Table 1-1] [Table 1-2]
[0070] Performance test:
[0071] (1) Resistivity of positive electrode active material: The positive electrode active material powder was measured at a pressure of 20 MPa using a powder resistance meter.
[0072] (2) Gram capacity of positive electrode active material:
[0073] The batteries produced in the examples and comparative examples were charged at 25° C. at a rate of 0.1 C to 4 V, and discharged at a rate of 0.1 C to 1 V, to perform a full charge / discharge test, and the discharge capacity was obtained as the gram capacity of the material.
[0074] (3) Battery cycle performance: The batteries prepared in the examples and comparative examples were charged at 25°C up to 4 V at a rate of 0.1 C until the capacity of the sodium ion battery became less than 80% of the initial capacity, and then discharged down to 1 V at a rate of 0.1 C to perform a full charge / discharge cycle test, and the number of cycles was recorded. The test results are shown in Table 2. [Table 2]
[0075] As can be seen from Examples 1 to 4, there is a slight difference in the gram capacity and the number of cycles of the batteries made from the positive electrode active materials having different compositions. Optionally, the positive electrode active material is Na4Fe3(PO4)2(P2O7).
[0076] As can be seen from Examples 5-9 and Comparative Examples 1-2, when the mass content of the shell layer material in the positive electrode active material is within the range of 1%-10%, the gram capacity, dynamic characteristics and cycle performance of the battery are good. When the mass content of the shell layer material in the positive electrode active material is too high, the thickness of the shell layer is too high, the mass ratio of the conductive polymer is too high, and the mass ratio of the phosphate group sodium salt material with good cycle performance in the core layer material is small, which ultimately affects the cycle performance of the battery. When the mass content of the shell layer material in the positive electrode active material is too low, the coating layer of the conductive polymer coated on the core layer material is too thin, the conductivity of the positive electrode active material is reduced, and the surface of the positive electrode active material is easily in direct contact with the electrolyte, which causes side reactions to occur violently. Optionally, the mass content of the shell layer material in the positive electrode active material is 4%-8%.
[0077] As can be seen from Examples 10 to 14 and Comparative Examples 3 to 4, when the mass content of the conductive substrate in the positive electrode active material is within the range of 1% to 10%, the battery life is long. When the mass content of the conductive substrate in the positive electrode active material is too high, the amount of carbon material with a large specific surface area, no capacity, and low compaction density becomes too large, the battery capacity becomes small, and the energy density and cycle life of the battery are reduced. When the mass content of the conductive substrate in the positive electrode active material is too low, the conductive network between the active materials is difficult to effectively form, the conductive speed of the battery is reduced, the gram capacity of the active material is difficult to exert, and the battery life is reduced. Optionally, the mass content of the conductive substrate in the positive electrode active material is 4% to 8%.
[0078] As can be seen from Examples 15 to 17, the selection of the conductive polymer type affected the gram capacity and cycle life of the battery. Optionally, the shell layer material may be polypyrrole.
[0079] As can be seen from Examples 18 to 22 and Comparative Examples 5 to 6, when the average particle diameter of the positive electrode active material is within the range of 5 μm to 20 μm, the gram capacity and cycle performance of the battery are the best. When the average particle diameter of the positive electrode active material is too small, aggregation is likely to occur and side reactions with the electrolyte become intense. When the average particle diameter of the positive electrode active material is too large, the diffusion rate of the active ions inside the material is reduced, the dynamic properties are reduced, and the gram capacity and cycle performance of the battery are affected. Optionally, the average particle diameter Dv50 of the positive electrode active material satisfies 8 μm≦Dv50≦15 μm.
[0080] As can be seen from the data of Examples 1 to 22 and Comparative Example 7, in Examples 1 to 22, the gram capacity of the positive electrode active material and the cycle life of the battery were slightly affected by changes in the conductive substrate mass fraction, the type of shell layer material, and the particle size of the positive electrode active material. However, in Comparative Example 7, which was compared, the surface of the core layer material was not coated with a shell layer material, so the conductivity of the positive electrode active material was reduced, the resistivity increased, and the gram capacity of the material was significantly reduced. In addition, the core layer material came into direct contact with the electrolyte, causing side reactions to occur intensively, and the cycle performance of the battery was reduced.
[0081] Although the present application has been disclosed above with preferred embodiments, it does not limit the scope of the claims, and a person skilled in the art can make some possible changes and modifications without departing from the concept of the present application, therefore, the protection scope of the present application shall be in accordance with the scope defined by the claims of the present application.
Claims
1. A conductive substrate, and an active material having a core-shell structure composed of a core layer material and a shell layer material, the active material being distributed on the conductive substrate; wherein the core layer material comprises a phosphate-based sodium salt material, the shell layer material comprises a conductive polymer, and the conductive substrate comprises a carbon material, and the positive electrode active material has at least one of the following characteristics: (1) The chemical formula of the sodium phosphate material is Nax1Ry1(PO4)Z1, where 1≦x1≦3, 1≦y1≦2, 1≦z1≦3, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb; (2) The chemical formula of the sodium phosphate material is Nax2Ry2(P2O7)Z2, where 1≦x2≦7, 1≦y2≦3, and 1≦z2≦4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb; (3) The chemical formula of the sodium phosphate material is Nax3Ry3(PO4)Z3(P2O7)k3, where 1≦x3≦7, 1≦y3≦4, 1≦z3≦2, 1≦k3≦4, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb; (4) The chemical formula of the phosphate group sodium salt material is Nax4Ry4(PO4)Z4Ml1, where 1≦x4≦3, 1≦y4≦2, 1≦z4≦2, and 1≦l1≦3; R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb; and M includes at least one of F, Cl, and Br; the conductive polymer includes at least one of polyaniline, polypyrrole, a polymer of 3,4-ethylenedioxythiophene monomer, and polyethylene oxide; The mass content of the shell layer material in the positive electrode active material is 1% to 10%, the mass content of the conductive base material in the positive electrode active material is 1% to 10%, and the average particle diameter of the positive electrode active material is 5 μm to 20 μm. Positive electrode active material.
2. The sodium phosphate salt material is NaFePO 4 , Na 3 V 2 (P.O. 4 ) 3 , Na 2 FeP 2 O 7 , Na 2 MnP 2 O 7 , NaCoP 2 O 7 , Na 7 V 3 (P 2 O 7 ) 4 , Na 2 FePO 4 F, Na 3 V 2 (P.O. 4 ) 2 F 3 , Na 4 Fe 3 (P.O. 4 ) 2 (P 2 O 7 ), Na 4 Mn 3 (P.O. 4 ) 2 (P 2 O 7 ), Na 4 Co 3 (P.O. 4 ) 2 (P 2 O 7 ), Na 4 Ni 3 (P.O. 4 ) 2 (P 2 O 7 ), Na 7 V 4 (P.O. 4 ) (P 2 O 7 ) 4 The positive electrode active material of claim 1 , comprising at least one of:
3. 10. The positive electrode active material of claim 1, having at least one of the following characteristics: (5) The thickness of the shell layer material is 50 nm to 400 nm. (7) The mass content of the core layer material in the positive electrode active material is 90% to 99%.
4. 10. The positive electrode active material of claim 1, having at least one of the following characteristics: (8) The carbon material includes at least one of carbon nanotubes, graphene, carbon fibers, natural graphite, and artificial graphite. (9) The carbon material contains an oxygen-containing group, and the oxygen-containing group is at least one type selected from a carboxyl group, a hydroxyl group, and an ether group. (10) The carbon material contains an oxygen-containing group, and the mass content of oxygen atoms in the carbon material is ≧0.1%. (11) The conductive substrate is a carbon material.
5. 10. The cathode active material of claim 1, wherein the cathode active material has at least one of the following characteristics: (12) The positive electrode active material has a resistivity of 0.005 Ω·cm to 100 Ω·cm at a pressure of 20 MPa. (14) The gram capacity of the positive electrode active material is 100 mAh / g to 180 mAh / g.
6. An electrochemical device comprising a positive electrode sheet containing the positive electrode active material according to any one of claims 1 to 5, a negative electrode sheet, a separator, and an electrolyte.
7. An electronic device comprising the electrochemical apparatus of claim 6.
Citation Information
Patent Citations
Olivine sodium iron phosphate with polymer coating, sodium iron battery comprising the same as cathode material, and process thereof
KR1020160136809A
Electrode Active Material and Method for Preparing the Same
KR1020200109991A
Positive electrode for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
WO2017195332A1
